What is restrained eating and how do we identify it?. (1st December 2020) - Polivy, Janet; Herman, C. Peter; Mills, Jennifer S.
Abstract: Defining and measuring such qualities as restrained eating or dieting may require more than simply administering questionnaires and assuming that we are identifying the population that we wish to study. Different questionnaires may identify different types of restrained eaters, and even deciding what restrained eating consists of is a complicated endeavor. We discuss how to define and measure restrained eating, specifying key attributes, and acknowledging the problems inherent in relying on self-report instruments. We conclude that given the difficulties in defining such constructs as restrained eating, we need to specify more clearly exactly what our research questions are, in order to be sure that we are identifying the populations with the attributes necessary to answer those questions.